Hirudotherapy in complex treatment of chronic heart failure - L. P. Kusnetsova; V. A. Lusov; N. A. Volov; N. A. Smirnova; L. S. Bogdanova (Российский кардиологический журнал, 2008)
In total, 70 patients with coronary heart disease (CHD) and Functional Class II-III(NYHA) chronic heart failure (CHF) were administered standard treatment combined with hirudotherapy. In more than 50% of the participants, dyspnoea and peripheral edema reduction, plus increased physical stress tolerance, were observed. In hypertensive patients, diastolic blood pressure significantly decreased, and ejection fraction increased. Hemostasis changes manifested in reduced platelet aggregation and normalized fibrinogen and SFMC levels.